Correlation of Legal Presumption and Legal Norm - Virabyan, Gevorg (Bulletin of Yerevan University C: Jurisprudence, 2021)
In legal doctrine, the problem of the correlation between a legal presumption and a legal norm is by no means new. The subject of scientific debate, formed by two points of view, is whether a legal presumption is a legal norm or not. In particular, one group of scientists is inclined to equate a legal presumption with a legal norm, while another group tries to deny the identification of the latter. In other words, jurists cannot develop a unified approach to this problem, which, naturally, prevents the development of the concept of a general theory of integration of sectoral approaches to legal presumptions.Regarding the problem under discussion the author adheres to an approach that does not identify a legal presumption with a legal norm. Therefore, in order to develop the concept of a general theory of integrating sectoral approaches to legal presumptions within the framework of this article, the author first turned to the existing approaches on the correlation between a legal presumption and a legal norm, the advantages and disadvantages of the latter, and then tried to solve this problem within the framework of the instrumental theory of law; (1) a general description of a legal norm as a legal measure was presented, listing the differences between a legal norm and a legal presumption, (2) the correlation between a legal norm and a legal presumption as an auxiliary legal measure was discussed.
Keywords: legal presumption; legal norm; instrumental theory of law; legal measure; rule of conduct; civil legal norm; regulatory prescription; civil legal presumption; legal fact; auxiliary legal measure; legal system; subjective rights and obligations